Forensic psychology and law - Roesch, Ronald (John Wiley & Sons)
Introduction to psychology and law: civil and criminal applications -- Forensic assessment in criminal domains -- Forensic assessment in civil domains -- Forensic treatment -- Eyewitness identification -- Police investigations, interrogations, and confessions -- Juries and legal decision making -- Juveniles in the legal system -- Police psychology -- Correctional psychology -- Psychology, law, and public policy -- Ethics and professional issues